The impact of the crime of bribery on economic development - Recioui, Messaouda; Chenini, Rachid (International journal of economic perspectives, 2025)
This research examines the profound and multidimensional negative impact of the crime of bribery on economic development in any country, focusing on the economic dimensions rather than merely the ethical or legal aspects. The study demonstrates how bribery constitutes a major obstacle to achieving sustainable growth. The analysis explores the main mechanisms through which bribery distorts the course of economic progress, including the misuse of public resources. In such cases, funds are diverted toward less productive and more corruption-prone projects, resulting in weak infrastructure and higher costs. Bribery also stands as a major barrier to both domestic and foreign investment, as it creates an unstable business environment burdened with additional illegal costs, thereby undermining confidence in the economy. Moreover, the study highlights bribery’s impact on institutional systems and the rule of law, where it weakens property rights and exacerbates the public’s lack of trust in government, ultimately eroding its legitimacy. The effects of bribery are particularly severe on vulnerable groups, acting as a regressive tax that worsens poverty and deepens social inequality. It also leads to the deterioration of essential public services such as healthcare and education, thereby undermining human capital development. Additionally, bribery stimulates the growth of the informal economy and reinforces systemic inefficiencies. Empirical evidence consistently confirms a strong correlation between high levels of bribery and lower economic growth rates, reduced global competitiveness, and deteriorating infrastructure quality.